An Empirical Analysis of Bankruptcy Risk in Oil and Gas Companies - Bayramova, Sevinj (2016)
In this thesis, we firstly presented a deep analysis of different bankruptcy prediction models, aiming to find out which model provides more accurate predictions. Secondly, we conducted an empirical analysis to determine the main factors led to the recent crisis in oil and gas industry, using a sample of 240 oil and gas companies from U.K., U.S. and Canada markets. We sought to develop a comprehensive model to forecast default probability, and we are particularly interested in incorporating the financial, macroeconomic, risk management and corporate governance variables into the same model in order to find out all possible internal and external factors that causing corporate bankruptcy. To the best of our knowledge, this is the first study to account for study to account for risk management and corporate governance bankruptcy prediction literature. As a result of our research we found that the profitability, leverage, liquidity, firm size, risk management, corporate governance and macroeconomic changes are all significant determinants of bankruptcy.